The Development of Cirebon Ethnoscience-Based Thematic-Integrated Book of â€œSelalu Berhemat Energiâ€ (Journal of Primary Education, 2019)
This study aimed to find out the process of developing a Cirebon ethnoscience-based thematic-integrated book for primary 4 students with the theme â€œSelalu Berhemat Energiâ€ along with itsâ€™ validity. This study applied development technique of ADDIE that consists of five stages: (1) analysis, (2) design, (3) develop, (4) implement, and (5) evaluate (Branch, 2010). The analysis stage was carried out by taking theoretical review and field data through questionnaires and interview conducted to teachers and principals from four schools in Cirebon which have implemented 2013 curriculum. It was found from the respondents that they have not integrated Cirebonâ€™s culture into the learning process except Art. Thus, students have comprehension on their own culture. Prototypes of the product were then created as the basis of the product development. Through the validation process and suggestions from the validators, the product then developed into an ethnoscience-based of thematic-integrated book entitled â€œSelalu Berhemat Energiâ€ with batik mega mendung taken as the main learning material of the developed book.